INTEGRATING LOCAL WISDOM INTO SCHOOL COUNSELING SERVICES: A PEDAGOGICAL APPROACH TO STUDENTS’ SOCIAL DEVELOPMENT - Jarkawi Jarkawi; Emilda Prasiska; Akhmad Rizkhi Ridhani (Nurul Jadid University, 2026)
This study aims to describe the integration of local wisdom in the management of social counseling services at Madrasah Aliyah in Banjarmasin City and analyze its contribution to the formation of students' social behavior. The study used a qualitative approach with a case study method through in-depth interviews, participatory observation, and documentation. The results showed that local values such as manuntung (never give up spirit), sasanggan (mutual cooperation), and basopan (politeness) were systematically integrated in the planning, implementation, and evaluation stages of counseling services. Counselors developed a narrative approach based on local values so that the counseling process became more contextual, close to students' cultural experiences, and more easily internalized in everyday life. This integration resulted in increased positive social behaviors in students, such as responsibility, empathy, social awareness, and the ability to work together. This study contributes to expanding the study of local culture-based counseling service management by demonstrating that local wisdom functions not only as a complement to moral values, but also as an effective pedagogical and counseling strategy to strengthen student character formation in the madrasah environment.